CHILDHOOD THYROTOXICOSIS - TAHER, M.A. (The ASEAN Journal of Radiology, 2023)
Most of the thyrotoxic patients are adult and it is rare (about 1% of adult) in childhood. This rarity prompts us to report these two cases (both girl, age 10 & 12 years) found recently, confirmed by radioiodine uptake (RAIU), radioassay of thyroid related hormones (T,, T, TSH levels) and both of them had been followed upto clinical cure by carbimazole and radioiodine (I-131) therapy.